Simultaneous fluorescence imaging of selenol and hydrogen peroxide under normoxia and hypoxia in HepG2 cells and in vivo. Issue 40 (26th April 2016) - Liu, Xiaojun; Hu, Bo; Cheng, Ranran; Kong, Fanpeng; Pan, Xiaohong; Xu, Kehua; Tang, Bo
Abstract : Simultaneous fluorescence imaging of selenol and hydrogen peroxide with 5-FAM-peptide-AuNPs and QCy7-H2 O2 was realized during tumor cell apoptosis induced by selenite. Abstract : Based on the rapid substitution reaction of the Au–S bond by selenol, we designed and synthesized a nanoprobe 5-FAM-peptide-AuNPs for selenol. Real-time imaging shows that this probe together with the molecular probe QCy7-H2 O2 is able to simultaneously and differentially monitor the concentrations of selenol and H2 O2 in living cells and in vivo .